The role of ferroptosis-related non-coding RNA in liver fibrosis - Zhang, Guozhu; Wu, Kejia; Jiang, Xiaobo; Gao, Yuan; Ding, Dong; Wang, Hao; Yu, Chongyuan; Wang, Xiaozhong; Jia, Naixin; Zhu, Li (Frontiers in Cell and Developmental Biology, 2024)
Liver fibrosis represents a reversible pathophysiological process, caused by chronic inflammation stemming from hepatocyte damage. It delineates the initial stage in the progression of chronic liver disease. This pathological progression is characterized by the excessive accumulation of the extracellular matrix (ECM), which leads to significant structural disruption and ultimately impairs liver function. To date, no specific antifibrotic drugs have been developed, and advanced liver fibrosis remains largely incurable. Liver transplantation remains the sole efficacious intervention for advanced liver fibrosis; nevertheless, it is constrained by exorbitant costs and the risk of postoperative immune rejection, underscoring the imperative for novel therapeutic strategies. Ferroptosis, an emergent form of regulated cell death, has been identified as a pivotal regulatory mechanism in the development of liver fibrosis and is intricately linked with the progression of liver diseases. Recent investigations have elucidated that a diverse array of non-coding RNAs (ncRNAs), including microRNAs, long non-coding RNAs, and circular RNAs, are involved in the ferroptosis pathway, thereby modulating the progression of various diseases, including liver fibrosis. In recent years, the roles of ferroptosis and ferroptosis-related ncRNAs in liver fibrosis have attracted escalating scholarly attention. This paper elucidates the pathophysiology of liver fibrosis, explores the mechanisms underlying ferroptosis, and delineates the involvement of ncRNA-mediated ferroptosis pathways in the pathology of liver fibrosis. It aims to propose novel strategies for the prevention and therapeutic intervention of liver fibrosis.